Quality of life patients with type 2 diabetes among patients aged 65-75 years - Bąk, Ewelina; Kober, Lukas; Fiedler-Siwek, Ewelina (Journal of Education, Health and Sport, 2025)
Introduction: Type 2 diabetes is a chronic disease that contributes to the occurrence of limitations in the patient’s life. In order to assess the quality of life of patients with diabetes, the following aspects should be taken into account: age, gender, education, presence of complications, Material and methods: The study was conducted using the diagnostic survey method. The research tools were: a survey questionnaire consisting of metrics and clinical parameters, the ADDQoL questionnaire, The study was conducted on a group of 104 patients (including 58 women and 46 men) in the Diabetes Clinic at the Provincial Hospital in Bielsko-Biała in the period from April 20, 2018 to September 1, 2018. Results: Diabetes has been shown to have a negative impact on all 19 ADDQoL domains. The most negative feelings concern the future, freedom in eating, and enjoying leisure activities. Conclusions: Patients with type 2 diabetes have a negative impact on their quality of life. Patients with diabetes require greater focus on educational activities aimed at adhering to a rational diet and psychological support.